2007
DOI: 10.1089/cap.2007.0112
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone-Induced Priapism in a 12-Year-Old Boy with Schizophrenia

Abstract: Objective: To examine whether adverse perinatal experiences of children are associated with obsessive compulsive disorder (OCD) in youth. Methods: Subjects were 130 children and adolescents with OCD recruited from a family genetic study of pediatric OCD and 49 matched controls from a contemporaneous family case-control study of attention-deficit/hyperactivity disorder (ADHD). Subjects were comprehensively assessed in multiple domains of function. A systematic history of pregnancy, delivery, and infancy complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…In agreement with our findings, two other studies (Geller et al, 2008; Vasconcelos et al, 2007) found that prolonged labor was associated with OCD diagnosis; also, our finding regarding forceps delivery and OCD diagnosis is in line with one other study (Santangelo, 1994). However, our results regarding co-occurring OCD are in contrast to Mathews et al (Mathews et al, 2006) who had identified maternal smoking as the most important exposure.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our findings, two other studies (Geller et al, 2008; Vasconcelos et al, 2007) found that prolonged labor was associated with OCD diagnosis; also, our finding regarding forceps delivery and OCD diagnosis is in line with one other study (Santangelo, 1994). However, our results regarding co-occurring OCD are in contrast to Mathews et al (Mathews et al, 2006) who had identified maternal smoking as the most important exposure.…”
Section: Discussionsupporting
confidence: 94%
“…Obsessive-compulsive disorder and schizophrenia are, in fact, considered to be neurodevelopmental disorders with dysfunctional frontal subcortical circuitry 37. A possible common neurodevelopmental origin is suggested by several lines of evidence: both obsessive-compulsive disorder and schizophrenia have a juvenile onset and chronic course; relevant neurological soft signs are present in both diseases;38,39 patients with obsessive-compulsive disorder and those with schizophrenia have more adverse perinatal experiences than healthy controls;38,40 obsessive-compulsive symptoms are clinically important phenomena in people with schizophrenia; and people with obsessive-compulsive disorder often experience psychosis 41. In line with this theory, the impaired capacity to experience and express emotions may be seen as another chronic consequence of the same neurodevelopmental origin of the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed recruitment and study methodology is reported elsewhere [31]. In brief, as part of a large pediatric OCD family study, 130 probands and 374 first degree relatives were recruited mostly via referrals to a pediatric OCD program (22 families were ascertained directly through advertising).…”
Section: Methodsmentioning
confidence: 99%